ตัวแบบพยากรณ์ปริมาณการส่งออกมะม่วงของประเทศไทย: Forecasting Model for Mango Export Volumes of Thailand - Choopradit, Boonyarit; Chaipitak, Saowapa (Asian Health, Science and Technology Reports, 2018)
งานวิจัยนี้มีวัตถุประสงค์เพื่อสร้างตัวแบบพยากรณ์ที่เหมาะสมกับอนุกรมเวลาปริมาณการส่งออกมะม่วงรายเดือนของประเทศไทย โดยใช้ข้อมูลจากสำนักงานเศรษฐกิจการเกษตร กรมส่งเสริมการเกษตร กระทรวงเกษตรและสหกรณ์ ตั้งแต่เดือนมกราคม พ.ศ. 2550 ถึงเดือนธันวาคม พ.ศ. 2559 จำนวนทั้งสิ้น 120 ค่า โดยแบ่งข้อมูลออกเป็น 2 ส่วน ส่วนแรกร้อยละ 90 และส่วนหลังร้อยละ 10 โดยส่วนแรกนำมาสร้างตัวแบบพยากรณ์ด้วยวิธีการพยากรณ์ 3 วิธีได้แก่ วิธีแยกองค์ประกอบ วิธีโฮลต์-วินเตอร์ และวิธีบอกซ์-เจนกินส์ และส่วนหลังนำมาตรวจสอบความถูกต้องของค่าพยากรณ์ โดยใช้เกณฑ์ค่าร้อยละความคลาดเคลื่อนสัมบูรณ์เฉลี่ยและเกณฑ์ค่ารากที่สองของความคลาดเคลื่อนกำลังสองเฉลี่ยต่ำที่สุด ผลจากการวิจัยพบว่าวิธีบอกซ์-เจนกินส์เป็นวิธีที่มีความถูกต้องมากที่สุดโดยมีตัวแบบเป็น SARIMA(0,1,2)(0,1,1)12 The objective of this research was to construct the most suitable forecasting model for the monthly mango export volumes of Thailand. The monthly export volumes were gathered from the Office of Agricultural Economics, Department of Agricultural Extension, Ministry of Agriculture and Cooperatives from January 2007 to December 2016 (120 values) and divided into two parts (90% and 10%). The first part was applied for constructing the forecasting models by three methods consisting of decomposition, Holt-Winters and Box-Jenkins methods. The second part was used for comparing the accuracy of the forecasts by considering the mean absolute percentage error (MAPE) and root mean squared error (RMSE). The results have been shown that Box-Jenkins is the best method to predict the mango export volumes with the lowest MAPE and RMSE and the appropriate forecasting model is SARIMA(0,1,2)(0,1,1)12.